X-Men hellfire gala - immortal - Duggan, Gerry; Foxe, Steve; Wells, Zeb 1977- (Marvel Worldwide, Inc., 2022)
Don your dazzling dresses and tailored tuxedos -- it's time for the second annual Hellfire Gala! And the highlight will be the election of a new team of X-Men! But can Emma Frost hold everything together when a shocking revelation threatens to derail her big night? Meanwhile, a nefarious party crasher leads to a high-stakes mission for Wolverine and Spider-Man! Plus: Cannonball and Sunspot lead their fellow runners-up from last year's X-Men election on a secret mission in aid of the Shi'ar Empire!
Contains material originally published in magazine form as X-MEN: HELLFIRE GALA (2022) #1, THE SECRET X-MEN (2022) #1, X-MEN UNLIMITED INFINITY COMIC (2021) #50-55, X-MEN: HELLFIRE GALA CONFESSIONALS, FREE COMIC BOOK DAY 2022: AVENGERS/X-MEN #1 and AMAZING SPIDER-MAN (2022) #9
Keywords: X-Men (Fictitious characters) / Comic books, strips, etc; Avengers (Fictitious characters) / Comic books, strips, etc; Spider-Man / (Fictitious character) / Comic books, strips, etc; Mutation (Biology) / Comic books, strips, etc; X-Men (Personnages fictifs) / Bandes dessinées; Avengers (Personnages fictifs) / Bandes dessinées; Mutation (Biologie) / Bandes dessinées; Spider-Man / (Fictitious character); Avengers (Fictitious characters); Mutation (Biology); X-Men (Fictitious characters); superhero comics; Comics (Graphic works); Graphic novels; Science fiction comics; Superhero comics; Bandes dessinées de superhéros; Bandes dessinées de science-fiction; Bandes dessinées; Comic